The Effect of Current Ratio and Debt to Asset Ratio on Net Profit Margin at PT Hutama Karya (Persero) - Aliah Pratiwi; Eka Putri Ningsih; Mujiburrahman (Invoice : Jurnal Ilmu Akuntansi, 2025)
This study investigates the effect of the Current Ratio (CR) and Debt to Asset Ratio (DAR) on the Net Profit Margin (NPM) of PT Hutama Karya (Persero), a state-owned enterprise in Indonesia’s construction sector. Employing a quantitative associative research design, the study analyzes financial data extracted from audited annual reports covering 2014–2023. The variables examined include current assets, total liabilities, and net income after tax. Purposive sampling was applied to ensure the selection of relevant and complete data, while data analysis was conducted using SPSS software with a 5% significance level. The results reveal that CR and DAR, individually, do not significantly influence NPM. Furthermore, simultaneous testing confirms that both ratios collectively have no significant impact on profitability. The findings suggest that short-term liquidity and leverage are not primary determinants of net profit performance in PT Hutama Karya (Persero) during the observed period. This outcome may be attributed to the company’s long-term project investments, government-backed financing schemes, and operational strategies that prioritize large-scale infrastructure development over liquidity optimization. The study highlights the need for management to focus on operational efficiency, cost control, and effective project execution to enhance profitability. For future research, it is recommended to examine additional financial and operational variables, such as Return on Equity (ROE), Debt to Equity Ratio (DER), and Working Capital Turnover (WCT), to provide a more comprehensive understanding of profitability determinants in state-owned construction enterprises. These insights contribute to both academic literature on financial performance and practical decision-making in managing complex SOEs engaged in strategic national projects.